Inhaling and lung cancer: an anomaly explained. - Wald, N; Idle, M; Boreham, J; Bailey, A (1983)
An objective index of inhaling cigarette smoke based on carboxyhaemoglobin concentrations and the carbon monoxide yields of cigarettes was used to investigate possible systematic differences in the extent of inhaling among light and heavy smokers when classified according to their self described inhaling habits. A total of 2108 men who smoked cigarettes were studied. Heavy smokers (20 or more cigarettes a day) had a higher average inhaling index than light smokers (fewer than 20 cigarettes a day) both among those who said that they inhaled and among those who said that they did not. This observation, together with indirect evidence that heavy smokers who inhale deeply may to some extent avoid depositing smoke condensate on their main bronchial epithelium, explains a hitherto unresolved anomaly--namely, that the risk of lung cancer is less among heavy cigarette smokers who say that they inhale than it is among those who say that they do not inhale.